Análise epidemiológica dos hipertensos da Unidade Básica de Saúde da Família Dra Márcia Guedes de Sá Earp – Campo Grande MS - CÂMARA, Juliana Viana; FREITAS, Tânia Christina Marchesi; CÂMARA, Sônia Aparecida Viana (ANAIS DO ENIC, 2018)
-